2016
DOI: 10.1098/rsob.160057
|View full text |Cite
|
Sign up to set email alerts
|

The missing link: does tunnelling nanotube-based supercellularity provide a new understanding of chronic and lifestyle diseases?

Abstract: Tunnelling nanotubes (TNTs) are increasingly recognized as central players in a multitude of cellular mechanisms and diseases. Although their existence and functions in animal organisms are still elusive, emerging evidence suggests that they are involved in developmental processes, tissue regeneration, viral infections or pathogen transfer, stem cell differentiation, immune responses as well as initiation and progression of neurodegenerative disorders and cancer (see Sisakhtnezhad & Khosravi 2015 Eur. J. Cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 81 publications
0
99
0
6
Order By: Relevance
“…As this is not the case, the selective transfer of whole, intact mitochondria remains the only possible explanation of our experimental data. The next step will be to investigate the mechanism of mitochondrial trafficking between cells in vivo, with tunnelling nanotubes being a plausible mode of intercellular transfer of the organelles (Rustom et al, 2004; Rogers and Bhattacharya, 2014; Rustom, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…As this is not the case, the selective transfer of whole, intact mitochondria remains the only possible explanation of our experimental data. The next step will be to investigate the mechanism of mitochondrial trafficking between cells in vivo, with tunnelling nanotubes being a plausible mode of intercellular transfer of the organelles (Rustom et al, 2004; Rogers and Bhattacharya, 2014; Rustom, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…This crosstalk is essential to disseminate signals and transfer cellular components, including metabolites and organelles, allowing a syncytial behaviour, not only in basal conditions, but also in response to external stimuli. Given the importance of a fine-tuned intercellular communication for the homeostasis of a healthy organism, its deregulation has been extensively associated with the development of several pathologies, such as cancer, cardiovascular diseases and age-related disorders (Aasen et al, 2016;Bang et al, 2015;Grek et al, 2014;López-Otín et al, 2013;Pitt et al, 2016;Rustom, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work by the same group have now demonstrated that horizontal mtDNA transfer from donor cells to mtDNA depleted cells enabled increased mitochondrial respiration, which was essential for these cells to form tumors (Berridge et al 2015; Dong et al 2017). These findings highlight new and exciting cellular mechanisms, such as nanotube transmission of mtDNA from one cell to another (Rogers and Bhattacharya 2013; Rustom 2016; Rustom et al 2004), that could be targeted to develop new and specific treatments of mitochondrial diseases.…”
Section: Promoting Mtdna Stabilitymentioning
confidence: 91%